Economic determinants of technological progress in G7 countries: A re-examination - (:unkn) unknown (ELSEVIER SCIENCE SA, 2012)
This study examines the relationship between technological change and a series of key macroeconomic variables in G7 countries. Basically, we find that the rate of interest has a negative impact on the pace of innovation, while investments in the R&D sector, high-technology exports, as well as net FDI inflows enhance technological change. The most surprising result of our analysis concerns the openness to trade ratio. Contrary to theoretical expectations and the findings of previous empirical studies. we were unable to find a positive or negative significant relationship between openness to trade and the rate of innovation in this study. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Technological change; Openness to trade; Triadic patent counts; Panel Poisson regression; UNIT-ROOT TESTS; PANEL-DATA; GROWTH